Loss of Choline Agonism in the Inner Ear Hair Cell Nicotinic Acetylcholine Receptor Linked to the α10 Subunit - Moglie, Marcelo J.; Marcovich, Irina; Corradi, Jeremías; Carpaneto Freixas, Agustín E.; Gallino, Sofía; Plazas, Paola V.; Bouzat, Cecilia; Lipovsek, Marcela; Elgoyhen, Ana Belén (Frontiers in Molecular Neuroscience, 2021)
The α9α10 nicotinic acetylcholine receptor (nAChR) plays a fundamental role in inner ear physiology. It mediates synaptic transmission between efferent olivocochlear fibers that descend from the brainstem and hair cells of the auditory sensory epithelium. The α9 and α10 subunits have undergone a distinct evolutionary history within the family of nAChRs. Predominantly in mammalian vertebrates, the α9α10 receptor has accumulated changes at the protein level that may ultimately relate to the evolutionary history of the mammalian hearing organ. In the present work we investigated the responses of α9α10 nAChRs to choline, the metabolite of acetylcholine degradation at the synaptic cleft. Whereas choline is a full agonist of chicken α9α10 receptors it is a partial agonist of the rat receptor. Making use of the expression of α9α10 heterologous receptors, encompassing wild-type, heteromeric, homomeric, mutant, chimeric and hybrid receptors, and in silico molecular docking, we establish that the mammalian (rat) α10 nAChR subunit underscores the reduced efficacy of choline. Moreover, we show that whereas the complementary face of the α10 subunit does not play an important role in the activation of the receptor by ACh, it is strictly required for choline responses. Thus, we propose that the evolutionary changes acquired in the mammalian α9α10 nAChR resulted in the loss of choline acting as a full agonist at the efferent synapse, without affecting the triggering of ACh responses. This may have accompanied the fine-tuning of hair cell post-synaptic responses to the high frequency activity of efferent medial olivocochlear fibers that modulate the cochlear amplifier.